Efisiensi Teknis Usahatani Tebu Rakyat (TR) Kategori Tanaman Plant Cane (PC) Pada Lahan Tegal di Kabupaten Malang, Provinsi Jawa Timur - Permadhi, Danang; Riyadi, Sahrul Dwi; Hanani, Nuhfil; Fahriyah, Fahriyah (Pusat Penelitian Perkebunan Gula Indonesia, 2024)
The objectives of this study were: (1) Analyse the technical efficiency (TE) of smallholder sugarcane farming (TR); (2) Analyse the factors that affect TE; and (3) Analyse the profitability of farming using the Sistem Bagi Hasil (SBH) and Sistem Pembelian Tebu (SPT) partnership schemes. This study was conducted in the PG-PG Malang working area with 31 smallholder sugarcane farmers surveyed in the 2022-2023 planting season. The method of measuring technical efficiency uses DEA (Data Envelopment Analysis), tobit regression, and analysis of sugarcane farming in each partnership scheme (SBH and SPT). The results of the analysis showed that the average TE value of TR farming on land was 97% and still had the potential to be increased by 3%. Factors that influence the level of TE are educational variables, family dependents and the role of financial institutions. If the average productivity of TR is 1,308 tonnes/ha, yield 5.11%, sugar price Rp.13,200/kg and sugarcane price Rp.72,000/kg. Then the actual and target average income and RC ratio values obtained in the SBH partnership are respectively Rp.18.17 million/ha (1.26) and Rp.20.41 million/ha (1.30), while in the SPT partnership respectively Rp.18.27 million/ha (1.23) and Rp.20.50 million/ha (1.26). Based on the RC ratio value, the recommended partnership scheme is SBH. However, fluctuations in sugarcane prices need to be considered, for example at the end of the milling season the price can reach Rp.95,000-Rp.100,000 per quintal and it is ensured that the income earned in the SBH scheme is higher than the RC ratio.